John Law’s Theory of Money and its roots in Scottish culture - Pittock, Murray G H (Proceedings of the Society of Antiquaries of Scotland, 2004)
This paper seeks to place the well-known lineaments of Law’s System in France within the context not only of his earlier writings on the Scottish economy but also in the dimension of his lived experience as a 17th-century Scot, the son of a goldsmith-banker, and a man acutely conscious both of the history of his country’s unstable monetary policy, and also of the final crisis into which it was lurching in his own day.